2000
DOI: 10.1039/b000948m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterisation, and molecular and electronic structure of CpMoCl2(R1CCR2) (R1, R2 = Ph, Et, Me): a new class of half-sandwich 17-electron molybdenum(III) organometallics

Abstract: Addition of alkyne to [CpMoCl2]2 affords compounds CpMoCl2(η 2 -alkyne) (alkyne = EtC≡CMe, 1; EtC≡CEt, 2; PhC≡CMe, 3; PhC≡CPh, 4) in good yields. The compounds have been characterised by C,H analyses, IR, EPR and mass spectroscopies, magnetic susceptibility, and cyclic voltammetry. In addition, a single crystal X-ray diffraction analysis has been carried out for compound 4. The alkyne ligand adopts an almost parallel conformation relative to the Cp ring, essentially identical with that of previously reported N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Theoretical studies showed that the SOMO of [MoCl 2 (h-HC 2 H)(h-C 5 H 5 )] is also partly Mo-Cl p* in character. 12 The angle X(1)-W(1)-X(2) in the cations 1 + -4 + and 6 + is very similar to that of the isoelectronic d 2 complex [NbCl 2 (h-PhC∫CMe)Tp¢] (102 • ), whereas in the neutral species 2, 4, 7 and 8 that angle is narrower (90-97 • ). The obtuse angle in [NbCl 2 (h-PhC∫CMe)Tp¢] was ascribed 17 to the alleviation of a destabilising interaction between a filled d xz orbital on the metal and a linear combination of p p Cl orbitals.…”
Section: X-ray Structural Studiesmentioning
confidence: 86%
See 2 more Smart Citations
“…Theoretical studies showed that the SOMO of [MoCl 2 (h-HC 2 H)(h-C 5 H 5 )] is also partly Mo-Cl p* in character. 12 The angle X(1)-W(1)-X(2) in the cations 1 + -4 + and 6 + is very similar to that of the isoelectronic d 2 complex [NbCl 2 (h-PhC∫CMe)Tp¢] (102 • ), whereas in the neutral species 2, 4, 7 and 8 that angle is narrower (90-97 • ). The obtuse angle in [NbCl 2 (h-PhC∫CMe)Tp¢] was ascribed 17 to the alleviation of a destabilising interaction between a filled d xz orbital on the metal and a linear combination of p p Cl orbitals.…”
Section: X-ray Structural Studiesmentioning
confidence: 86%
“…The 'orthogonal' alkyne orientation differs from that in the cyclopentadienyl analogue [MoCl 2 (h-PhC∫CPh)(h-C 5 H 5 )] where the C∫C bond is more nearly parallel to the C 5 ring. 12 Theoretical studies on [NbCl 2 (h-RC∫CR)Tp¢], 16 with the orthogonal arrangement, 17 For the redox pairs [WX 2 (h-PhC∫CPh)Tp¢] z (z = 0 or 1+, X = F or Cl) Db increases on reduction, with the alkyne aligned more closely with bond X(2)-W(1), by 18.2 and 12.9 • for X = F and Cl respectively. This alkyne alignment is also observed in the neutral molybdenum complexes 7 and 8 (Db = 40.9 and 20.8 • respectively).…”
Section: X-ray Structural Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Compound CpMo( 4 -C 4 H 6 )(CH 3 ) 2 , as well as analogues with different diene and alkyl groups, displays a reversible reduction, while the first oxidation is completely irreversible even at 1000 V . s -1 and a second oxidation is not observed 19 (see Table 3).…”
Section: (D) Electrochemical Studymentioning
confidence: 92%
“…We have recently reported the synthesis of three related redox pairs, namely [Cr(CO) 2 (h-PhC•CPh)(h-C 6 Me 6 )] z (z = 0, d 6 ; z = 1, d 5 ), [Mo(CO) 2 (h-PhC•CPh)TpA] z (z = 0, d 5 ; z = 1, d 4 5 formally by a sequence of steps involving one-electron oxidation followed by ligand substitution. Although not all members of this family tree have been identified for all of M, X and L there is sufficient evidence to suggest that the missing members may be chemically accessible.…”
mentioning
confidence: 99%